PENGARUH KEADILAN ORGANISASIONAL TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL PEGAWAI KONTRAK FAKULTAS EKONOMI UNIVERSITAS UDAYANA - Komang Ayu Indah Yuliani; Desak Ketut Sintaasih; I Gede Riana (STIMI Handayani Denpasar, 2016)
Human resource with highly organizational commitment in giving aquality servicing was a vital element and play an important role for organizationalsuccess. The aim of this study was to investigate the influence of organizationaljustice toward job satisfaction and organizational commitment. A sample as manyas 97 person of contract employees of Faculty of Economic and Business, UdayanaUniversity were used as respondent of study. Analyze method of the data used waspartial least square (PLS). The results of the study indicated that organizationaljustice influential positive and significant toward job satisfaction and organizationalcommitment, respectively. The job satisfaction also influential positive and significanttoward organizational commitment. The results showed that, more and more goodorganizational justice feld by the employees, so more and more good job satisfactionand organizational commitment. Likewise, more and more highly the job satisfactionof the employees, so more and more highly also the organizational commitment. Thisstudy parallel with the theory declared that the employees obtaining organizationaljustice would feel job satisfaction and more commit in doing their duties andfunctions. The practice implication of this study was could be used as material ofconsideration by manajemen in making policy and decision which interconnectedwith organizational justice which could increase job satisfaction and organizationalcommitment.